2008
DOI: 10.1037/h0100236
|View full text |Cite
|
Sign up to set email alerts
|

Experimental models for the evaluation of speech and public speaking anxiety: A critical review of the designs adopted.

Abstract: The objective of the present study was to identify articles related to experimental models for the evaluation of public speaking anxiety published in the literature from January 2000 to July 2006 and to analyze them regarding the designs proposed. The absence of a single model of evaluation was detected. Analysis revealed sensitivity of the model for the characterization of the role of the different patterns of anxiety present in the disorders studied. There was unanimous recognition of the sensitivity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
1
8
0
2
Order By: Relevance
“…It is important to stress that the most prevalent fear was that of public speaking, in agreement with the international literature [14][15][16][17] , demonstrating the relevance of this manifestation also within the Brazilian context.…”
Section: Methodssupporting
confidence: 60%
“…It is important to stress that the most prevalent fear was that of public speaking, in agreement with the international literature [14][15][16][17] , demonstrating the relevance of this manifestation also within the Brazilian context.…”
Section: Methodssupporting
confidence: 60%
“…Tais modelos têm sido amplamente utilizados em contextos de investigação clínico-experimental, sobretudo para avaliação da eficácia de psicotrópicos e intervenções psicoterapêuticas, mostrando-se para tal de grande valia [13][14][15][16] . Recentemente, realizou-se uma revisão de literatura 17 visando a investigar os delineamentos adotados nos estudos que utilizam tais modelos de simulação de falar em público. Constatou-se a carência de instrumentos padronizados e validados para a avaliação dos aspectos relativos à auto-avaliação do desempenho na tarefa e, principalmente, aos aspectos cognitivos relacionados à ansiedade e ao falar em público.…”
Section: Introductionunclassified
“…Physiological measurements including heart rate, blood pressure, and skin conductance are recorded throughout the test, as well as subjective data related to the degree of tension, anxiety, and fatigue experienced in each phase of the experiment. A literature review of studies using this experimental model (Osório et al, 2008c) revealed that instruments like the Visual Analogue Mood Scale (Folstein & Luria, 1973) and the StateTrait Anxiety Inventory (Spielberger et al, 1970) are often used to gauge subjective anxiety during the test, but that there are no standardized instruments available to assess cognitions associated with the experience. Therefore, our group has proposed an adapted version of the SSPS, the Self Statements during Public Speaking Scale -state version (SSPS-S), to be used as a subjective measure of cognitive aspects in experimental models of anxiety, especially the SPST (Osório et al, 2010c The SSPS-S proved sensitive to discriminate between SAD cases and non-cases throughout all the phases of the procedure, showing that cases make a lower positive assessment and a higher negative assessment of self and of their performance during public speaking as compared to non-cases.…”
Section: Fig 4 Experimental Model: Simulated Public Speaking Testmentioning
confidence: 99%